IN THE REGION OF 2014: THE DEPICTION OF THE INDONESIAN PRESIDENTIAL ELECTION IN THE POLITICAL CARTOONS (Jurnal Bahasa Lingua Scientia, 2024)
Cartoons have long been recognized as a highly effective means of conveying social and political messages in political communication. This paper presents a critical discourse analysis (CDA) of the intricate portrayal of the 2014 Indonesian presidential election in cartoons, using qualitative methods to unravel the underlying themes and narratives. The study aims to provide a comprehensive understanding of the multifaceted dimensions of this significant electoral event, shedding light on the nuanced perspectives and representations presented in the selected cartoons. A qualitative approach analyzed a diverse collection of political cartoons from reputable Indonesian newspaper and online media outlet, i.e., Kontan.id, during the period leading up to the 2014 presidential election. The CDA framework employed in this research allows for an in-depth examination of the visual and textual elements, unraveling the symbolic meanings, metaphors, and ideological underpinnings that shape the cartoons’ overarching messages. The study reveals how these political cartoons function as a complex form of visual rhetoric, reflecting the artists’ perspectives and the broader social and political climate surrounding the electoral process. The findings expose the dominant themes and recurring symbols used in the cartoons to portray the candidates, their policies, and the broader political landscape. The research examines the potential influence of these cartoons in shaping public opinion and political discourse during this crucial election period. The outcomes of this research offer valuable insights into the dynamics of political communication in Indonesia and shed light on the interplay between media, politics, and public opinion. By illuminating the portrayal of the 2014 Indonesian Presidential Election through the lens of political cartoons, this study contributes to a deeper understanding of the role of visual media in shaping political discourse and public perceptions during electoral campaigns. The implications of this research extend beyond the specific case of Indonesia, providing a framework for investigating the use of political cartoons in other electoral contexts worldwide.
Keywords: discourse; Indonesian; political cartoons; presidential election; visual rhetoric